Impaired driving and other Criminal Code driving offences: a practitioner's handbook - Jokinen, Karen (Criminal law series, 2023)
"In 2018, Parliament repealed and replaced all driving provisions of the Criminal Code, in part as a response to the enactment of the Cannabis Act. Impaired Driving and Other Criminal Code Driving Offences: A Practitioner's Handbook is a ... guide to this new legislation, designed to assist Crown and defence lawyers, as well as members of the judiciary. It explores all aspects of this area of law, including the different types of offences, the investigation process, provincial procedural differences, trial strategies and issues, sentencing, and ethics."--Provided by publisher.